Cerium(IV) Hexanuclear Clusters from Cerium(III) Precursors: Molecular Models for Oxidative Growth of Ceria Nanoparticles. Issue 38 (31st July 2015) - Mathey, Laurent; Paul, Mitali; Copéret, Christophe; Tsurugi, Hayato; Mashima, Kazushi
Abstract Reactions of cerium(III) nitrate, Ce(NO3)3⋅6 H2O, with different carboxylic acids, such as pivalic acid, benzoic acid, and 4‐methoxybenzoic acid, in the presence of a tridentate N, N, N‐donor ligand, diethylenetriamine (L1), under aerobic conditions yielded the corresponding cerium hexamers Ce6O8(O2CtBu)8(L1)4 (1), Ce6O8(O2CC6H5)8(L1)4 (2), and Ce6O8(O2CC6H4‐4‐OCH3)8(L1)4 (3). Hexamers 1, 2, and 3 contain the same octahedral CeIV6O8 core, in which all interstitial oxygen atoms are connected by μ3‐oxo bridging ligands. In contrast, treatment of the CeIV precursor (NH4)2Ce(NO3)6 (CAN) with pivalic acid and the ligand L1 under the same conditions afforded Ce6O4(OH)4(O2CtBu)12(L1)2 (4), exhibiting a deformed octahedral CeIV6O4(OH)4 core containing μ3‐oxo and μ3‐hydroxo moieties in defined positions. In contrast to the formation of 1–3, the use of N‐methyldiethanolamine (L) in the reaction with Ce(NO3)3⋅6 H2O and pivalic acid afforded a previously reported CeIII dinuclear cluster, Ce2(O2CtBu)6L2, even in the presence of dioxygen. ESI‐MS analysis of the reaction mixture clearly indicated the importance of the ligand L1 in promoting oxidation of the CeIII aggregates, [Cen(O2CtBu)3n(L1)2], which is necessary for the formation of CeIV hexamers.